The Safety of Probiotics Intended for Use in Pregnant and Lactating Women: From a Desirable to a Required Task - Leónides Fernández; Belén Orgaz; Juan M. Rodríguez (Foods)
During pregnancy, women undergo changes that affect virtually every organ, apparatus, or system, including the host microbiota. Most pregnancies progress smoothly despite the common presence of minor side-effects arising from such adaptations. However, some women may experience more serious complications, including gestational diabetes mellitus, preeclampsia, or preterm delivery. Probiotics are one of the products most used to try to prevent or treat any of the minor or severe symptoms or complications that women may experience during pregnancy or lactation; however, most of them have never been tested in such populations and, therefore, their efficacy and safety claims are frequently unsubstantiated. Overall, probiotic trials involving pregnant or lactating women have shown that these products are usually well-tolerated and safe although adverse effects may also exist. Therefore, health professionals attending pregnant or lactating women should be aware of their use and monitor their efficacy and safety. In conclusion, probiotics recommendations for pregnant or lactating women should be based on scientific evidence, opting exclusively for those products that have been designed for the specific target or condition that a pregnant or lactating woman may be experiencing or at risk of, and which efficacy and safety has already been convincingly tested in such populations.